Community Effectiveness RCT of a Comprehensive Psychosocial Treatment for High-Functioning Children With ASD. (29th March 2019) - Thomeer, Marcus L.; Lopata, Christopher; Donnelly, James P.; Booth, Adam; Shanahan, Andrew; Federiconi, Veronica; McDonald, Christin A.; Rodgers, Jonathan D.
Abstract : This community effectiveness randomized clinical trial examined the feasibility and effectiveness of a comprehensive psychosocial treatment, summerMAX, when implemented by a community agency. Fifty-seven high-functioning children (48 male, 9 female), ages 7–12 years with autism spectrum disorder participated in this study. The 5-week summerMAX treatment included instruction and therapeutic activities targeting social/social-communication skills, interpretation of nonliteral language skills, face-emotion recognition skills, and interest expansion. A behavioral program was also used to increase skills acquisition and decrease autism spectrum disorder symptoms and problem behaviors. Feasibility was supported via high levels of fidelity and parent, child, and staff clinician satisfaction. Significant treatment effects favoring the treatment group over waitlist controls were found on all 5 of the primary outcome measures (i.e., child test of nonliteral language skills and parent ratings of the children's autism spectrum disorder symptoms, targeted social/social-communication skills, broader social performance, and withdrawal). Staff clinician ratings substantiated the improvements reported by parents. Results of this randomized clinical trial are consistent with those of prior studies of summerMAX and suggest that the program was feasible and effective when implemented by a community agency under real-world conditions.